Imperatriz no fim do mundo: memórias dúbias de Amélia de Leuchtemberg (1992) – Um romance histórico contemporâneo de mediação - Gomes , Gislaine (2019)
Considering the evolution in the hybrid writing of history and fiction trajectory, focused on the re-significances of the past, the present research seeks to analyze the novel Imperatriz no fim do mundo: memórias dúbias de Amélia de Leuchtemberg (1992), by Ivanir Calado, under the theories about mediation contemporary historical novel (FLECK, 2006, 2017). We observed that, among the already discussed modalities of the gender until the first decade of the 21st century, Ivanir Calado’s novel, through (by) the critical Reading that installs from the Brazilian imperial past, has been already classified as a new Latin-American historical novel (SANTOS, 2000) and as a historical metafiction (SILVA, 2016). It takes us to analyze if the theories applied to the proposed classifications are consistent with the novel by whom it’s used. To the questions put in check about the categorizations already done to Calado’s novel (1992), we propound a new classification base on the most recent Brazilian studies about this hybrid gender. The corpus selected is in the instability of he current studies about the historical novel, as the critical and theorist bases of this hybrid writing require constant updates, due to the significant changes that work in the writing of the gender. The theories developed by Fleck (2017) about the productions inserted in the post-boom period, there are new possibilities of analysis that can contribute to the accuracy of these studies. The theoretician launches such a proposal by adding to the existing modalities another one which meets the specifications reigned in the current novels: the contemporary historical novel of mediation. Based on the studies proposals of the research group “Ressignificações do passado na América: processos de leitura, escrita e tradução de gêneros híbridos de história e ficção – vias para a descolonização” we evidence here the re-significances of historical characters and their actions on the most recent fiction. Thus, the Calado’s novel of 1992 is read under the mediation aspects of its hybrid historical narrative. This aspect reveals that the theories about the gender discussed, published until the end of the 90s, of the twentieth century, aren’t enough at all for the analysis of all the current novels. For this, we use the bibliographical revision, the presuppositions of Comparative Literature, the critical analysis of the fictional narrative and the theories about the hybrid genre of history and fiction. The theoretical assumptions that underlie the relations established in this research consider the studies of Hutcheon (1991), Menton (1993), Mata Induráín (1995), Aínsa (1997), Esteves (2011), Fleck to ensure the possibilities of the proposed revision.